The Implementation of Notary Inclusive Rights in The Frame of Law Enforcement As a Public Official - Lubis, Ikhsan; Siregar, Taufik; Koto, Ismail; Chansrakaeo, Ruetaitip; Sari Lubis, Duma Indah (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
This article aims to describe the implementation of a notary’s inclusive rights within the framework of carrying out his duties as a public official. The granting of attribution authority to a notary as a public official is a special assignment that is intentionally made based on laws and regulations with certain roles, functions, and authorities to provide legal services (law enforcement) to the public who need authentic written evidence and the other civil laws authorities, along with inclusive legal protection in the enforcement of duties of a notary. The research method used is juridical normative, in which analyzing a legal event occur and followed by the comparative study between the legal source material and the legal rules that govern it in practice. This study aims to find out what, how, and why the position of a notary is attached to inclusive rights in terms of various legal aspects according to the research topic. The results showed that the form of legal protection that is inclusive of notaries as general officials have been sufficiently regulated in the constitution of the Notary Commission as well as the right to disobey and the obligation to disobey notaries. In addition, the existence of the Notary Honorary Council as a tool for the organization of the Indonesian Notary Association as well as the Notary Supervisory Board and the Notary Honorary Council has strengthened the position of an inclusive notary through preventive measures in the context of fostering and supervising the ethics of notary behavior and the practice of carrying out the duties of the notary commission under the rules in UUJN and UUJN-P.